Modulating mechanical stability of heterodimerization between engineered orthogonal helical domains - Miao Yu (Nature Portfolio, 2020)
Mechanically stable specific heterodimerization formed with reversible bonds are used as a molecular anchorage in single-molecule force spectroscopy studies with unique mechanical properties. Here authors develop a variety of heterodimerization molecular systems with a range of mechanical stability from a set of recently engineered helix-heterotetramers.